Transverse rectus abdominis musculocutaneous flap (TRAM flap) - experimental model in rats - Ely,Pedro Bins (2003)
The objective of this paper was to report the use of an experimental model of the Transverse Rectus Abdominis Musculocutaneous flap (TRAM flap), in rats. Thirty male Wistar rats weighing 180 to 220 g were submitted to the TRAM flap procedure. This article reports on the use of the caudally based, right unipedicled TRAM flap.